Intervención optométrica en paciente de sexo femenino de 12 años de edad con astigmatismo corneal. - Moyano Salvador, Indira Stefania (2024)
The 12-year-old patient presented a decrease in visual acuity, both near and far, accompanied by symptoms such as headache, blurred and distorted vision, and burning photophobia, which affected her visual acuity and her ability to perform daily activities. After a thorough physical examination, the diagnosis of moderate corneal astigmatism was confirmed. The optometric treatment implemented focused on providing the patient with a solution that will improve her visual acuity and comfort. Corrective lenses were chosen to address corneal astigmatism, with a personalized prescription based on detailed evaluation of ocular refraction and corneal keratometry. In addition, Optometric controls were scheduled to evaluate the assessment of astigmatism and make adjustments as necessary. A significant improvement was observed in the patient's visual acuity with the use of corrective lenses. A reduction in the patient's symptoms was achieved, meaning that the treatment not only improved her visual acuity, but also relieved her symptoms.